Complex doping of group 13 elements In and Ga in caged skutterudite CoSb3. (15th February 2015) - Xi, Lili; Qiu, Yuting; Zheng, Shan; Shi, Xun; Yang, Jiong; Chen, Lidong; Singh, David J.; Yang, Jihui; Zhang, Wenqing
Abstract: The complex doping behavior of Ga and In in CoSb3 has been investigated using ab initio total-energy calculations and thermodynamics. The formation energies of void filling, Sb substitution and complex dual-site occupancy defects with different charge states, and their dependence on chemical potentials of species, were studied. Results show that Ga predominantly forms dual-site 2GaVF –GaSb defects and substitutes for Sb only at very high Fermi levels or electron concentrations. In, on the other hand, can play multiple roles in skutterudites, including filling in the crystalline voids, substituting for Sb atoms or forming dual-site occupancy, among which the fully charge-compensated dual-site defects (2InVF –InSb and 4InVF –2InSb ) are dominant. The equilibrium concentration ratio of impurities at void-filling sites to those at Sb-substitution sites for Ga-doped CoSb3 is very close to be 2:1, while this value markedly deviates from 2:1 for In-doped CoSb3 . The 2:1 ratio of Ga doping in CoSb3 leads to low electron concentration (∼2 × 10 19  cm −3 ) and makes the doped system a semiconductor.